Effect of Supplementation of Mannan Oligosaccharide on Biochemical Pro-file in SVVU T17 Crossbred Pigs (Indian Journal of Animal Production and Management, 2025)
The present study was conducted to investigate the effect of supplementation of mannan-oligosaccharide (MOS) on the biochemical profile in SVVU T17 crossbred pigs. Twenty-four SVVU T17 crossbred male grower pigs above 2 months of age were randomly divided into four groups with six piglets in each group, i.e., T0, T1, T2, and T3. The experiment was conducted for 45 days, and at the end of the experiment, blood samples were collected for estimation of the biochemical profile. There was a significant decrease (P
Keywords: mannan-oligosaccharide; Biochemical profile; SVVU T17 pig